Approximate Sum-Of-Products Design Based on Quantum-Dot-Cellular Automata Using Distributed Arithmetic - Putta Lakshmi Ganesh, Aluru Venkata Sai Krishna, Madala Bramhendra, Ngangbam Phalguni Singh (International Journal of Advanced Science and Technology, 2020)
This paper presents 16-bit improved Approximate Sum-of-Products (ASOP) which is designed to achieve better results in fields of area and delay. This approximate circuit helps in improving performance of the Distributed Arithmetic operations with reduced area and delay. Sum-of-Products circuits plays an important role in many digital signal processing applications. This proposed model is validated by utilizing Quantum-Dot Cellular Automata (QCA) method in Distributed Arithmetic operations. Approximate computing is used for improving the performances of the design. The proposed design shows improvement of (68.66 – 83.22) % in area. It is also observed that the proposed model achieves 11.11 % improvement in delay.Keywords:Approximate Sum-of-Products (SOP), Distributed Arithmetic, Quantum-Dot Cellular Automata (QCA), Approximate computing.